Kinematics Analysis and Applications - Mizrahi, Joseph (IntechOpen, 2019)
Numerous problems in engineering and biology can be described, characterized, and analyzed in kinematics terms. In classical machinery and robotics the most distinctive characteristic is constrained motion of multi-degree-of-freedom kinematic chains. Robotic arms and manipulators have become essential devices in industrial applications and medicine. This book provides the reader with an updated look at the current trends in kinematics methods and applications. Section 1 deals with kinematics of linkages and includes analysis of cam mechanisms and transformation of rotary motion into oscillation. Section 2 covers compliant mechanisms, whereby elastically deformable parts are part of the mechanism. Finally, Section 3 deals with kinematics of spacecrafts and satellites in the contexts of global navigation systems and of space robot analysis.